From modelling tools towards the market itself ‐an opportunity for sustainability assessment? - Kauko, Tom (International Journal of Strategic Property Management, 2010)
Market based analyses of residential property value traditionally fall within two broad research traditions: a ’more practical’ value analysis tradition and a ’more academic’ market analysis tradition. While there is a steady flow of information from the latter to the former direction, until recently very little such information diffusion has occurred from the former to the latter modelling tradition. In such a learning process, the value modelling performance could serve as a guideline for what kind of market model is valid and feasible for a given dataset with certain recognisable tendencies. On the other hand, the characterisation of particular market circumstances is a key determinant of real estate sustainability. A sustainable market generates a sustainable value, which then can be used as an attractiveness indicator in a broader sense; or in the opposite case, an unsustainable market diagnoses a problem in unsustainable value. First published online: 18 Oct 2010